Avaliação do status de zinco e da expressão gênica de metalotioneínas em pacientes com aterosclerose tratados com rosuvastatina - Dias, Paula Cristina Silveira (2011)
The study had as objective to evaluate the zinc status by means of dietary intake, zinc in plasma and in erythrocytes and the metallothionein gene expression in patients with atherosclerosis in use of rosuvastatin. The research involved 27 adult and elderly patients of both genders with atherosclerosis that were treated with rosuvastatin (10mg/day) during 4 months. We performed the dosage of lipids, glucose, AST and ALT, ultrasensitive C-reactive protein (hsCRP), plasmatic and erythrocyte zinc and 1 and 2 metallothionein gene expression. The assessment of body mass index (BMI) and abdominal circumference (AC) was performed, besides the analysis of dietary intake of patients. The majority of the evaluated patients presented overweight, before and after the treatment, with no significant difference between the times of the study. It was identified that the AC was significantly reduced in the group (p<0.05) after the intervention. The majority of the patients had intake below the recommendation of calories and fibers and above recommendation of proteins. The mono and polyunsaturated fats were adequate for the majority of the patients, however, the saturated fat and cholesterol were consumed in excess by a great part of the individuals. The intake of zinc was inadequate, being noticed an inadequacy of 100% in the male gender and of 84% in the female. After the treatment with rosuvastatin there was a significant reduction in the total cholesterol (TC) and LDL-c (p<0.01) and no alterations were observed in the HDL-c and triacylglycerols. It was also verified that the reduction of glycemia (p<0.05) and of hsCRP (p<0.01). The analysis did not demonstrate significant differences in the plasmatic and erythrocyte zinc concentration after the treatment. There was, after the treatment, reduction of the MT1F gene (p<0.05) without, however, occurring significant alterations in the MT2A gene. The treatment with rosuvastatin was effective in the reduction of TC and LDL-c, and promoted the reduction of inflammatory marker hsCRP. The zinc in the plasma and erythrocyte was not altered by the use of the medication and there was a reduction in the MT1F gene, possibly due to the reduction of inflammation. The majority of patients presented inadequate intake of zinc and this inadequacy did not have relation with the mineral parameters in plasma and erythrocytes or with the metallothionein gene expression